Derechos de información, medios de comunicación y democracia. - López López, Pedro (Revista General de Información y Documentación, 2001)
Tbis article deals witb the importance for democracy of information rights. The role played by mass-media communications, fundamental to the aforesaid rights, is likewise is likewise studied.
Keywords: Information rights; communication media; democracy; political com munication